Religious Moderation in Islamic Education as a Strategy for Strengthening the Character of Tolerance and Prevention of Violence - Ahmad Akbar Fauzi; Fadhilla Nangroe Anggraini; Ghifary Bimo Aryoseno; Muhammad Shobarin Syakur (Pendekar: Jurnal Pendidikan Berkarakter, 2026)
Abstract: The increasing intolerance, radicalism and identity-based violence among Indonesian youth underscores the urgency of how higher commitment to Islam education on tolerance. This research reveals the moderation of religious thought in Islamic education as a strategy for peace and conflict prevention in a pluralistic society. This study, employing a qualitative and desk-based research design, scrutinizes academic papers, books, policy papers, and university reports that observe religious moderation as well as character education in Indonesia. The analysis of data applied was the content analysis technique, by categorizing and coding the key themes contained in relevant literature to find patterns [which] support religious moderation [in Islamic education]. The findings imply that wasatiyah internalization in the curriculum, teaching methods, school culture and digital literacy efforts are indicators of inclusive and resilient character towards non-violence. This research connects religious moderation with structural-functional theory, also social learning theory. It calls for policy support, better teacher preparation and more empirical research to facilitate better implementation in the future.Abstrak: Meningkatnya intoleransi, radikalisme, dan kekerasan berbasis identitas di kalangan pemuda Indonesia menggarisbawahi urgensi komitmen yang lebih tinggi terhadap pendidikan Islam yang berfokus pada toleransi. Penelitian ini mengungkapkan moderasi pemikiran keagamaan dalam pendidikan Islam sebagai strategi perdamaian dan pencegahan konflik dalam masyarakat pluralistik. Studi ini, menggunakan desain penelitian kualitatif dan berbasis pustaka, meneliti makalah akademis, buku, makalah kebijakan, dan laporan universitas yang mengamati moderasi keagamaan serta pendidikan karakter di Indonesia. Analisis data yang diterapkan adalah teknik analisis isi, dengan mengkategorikan dan mengkodekan tema-tema utama yang terdapat dalam literatur terkait untuk menemukan pola yang mendukung moderasi keagamaan dalam pendidikan Islam. Temuan menunjukkan bahwa internalisasi wasatiyah dalam kurikulum, metode pengajaran, budaya sekolah, dan upaya literasi digital merupakan indikator karakter inklusif dan tangguh terhadap non-kekerasan. Penelitian ini menghubungkan moderasi keagamaan dengan teori struktural-fungsional, serta teori pembelajaran sosial. Hal ini menyerukan dukungan kebijakan, persiapan guru yang lebih baik, dan lebih banyak penelitian empiris untuk memfasilitasi implementasi yang lebih baik di masa mendatang.